Redox-active dendrimer-like oligoguanidines and their use in a proton-coupled electron transfer reaction - Steuer, Lena; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of organic chemistry, 2022)
Redox-active organic dendrimers are of interest for a variety of applications, e. g. as components in optoelectronic devices and energy-storage (battery) materials, and were also used to model enzymatic reactivity. Here, we report the first synthesis of redox-active dendrimer-like oligoguanidines, assembling six or twelve guanidino groups attached to aromatic cores in one molecule. The novel oligoguanidines, being strong electron donors, are characterized in their stable (neutral and dicationic) redox states. Redox processes occur preferrentially at the core, while the periphery provides highly Brønsted basic sites. The combined electron and proton acceptor properties of the molecules in their stable oxidized dicationic redox state motivate applications in proton-coupled electron transfer (PCET) processes. In this work, we test their application in a representative intramolecular oxidative aryl-aryl coupling reaction.
Gesehen am 28.04.2022